Molecular determinants for selective C25-hydroxylation of vitamins D2 and D3 by fungal peroxygenases. Issue 1 (24th August 2015) - Lucas, Fátima; Babot, Esteban D.; Cañellas, Marina; del Río, José C.; Kalum, Lisbeth; Ullrich, René; Hofrichter, Martin; Guallar, Victor; Martínez, Angel T.; Gutiérrez, Ana
Abstract : Regioselective hydroxylation of vitamin D by Agrocybe aegerita and Coprinopsis cinerea peroxygenases was investigated in an experimental and computational study. Abstract : Hydroxylation of vitamin D by Agrocybe aegerita and Coprinopsis cinerea peroxygenases was investigated in a combined experimental and computational study. 25-Monohydroxylated vitamins D3 (cholecalciferol) and D2 (ergocalciferol), compounds of high interest in human health and animal feeding, can be obtained through a reaction with both fungal enzymes. Differences in conversion rates, and especially in site selectivity, were observed. To rationalize the results, diffusion of D2 and D3 on the molecular structure of the two enzymes was performed using the PELE software. In good agreement with experimental conversion yields, simulations indicate more favorable energy profiles for the substrates' entrance in C. cinerea than for A. aegerita enzyme. On the other hand, GC-MS analyses show that while a full regioselective conversion of D2 and D3 into the active C25 form is catalyzed by C. cinerea peroxygenase, A. aegerita yielded a mixture of the hydroxylated D3 products. From the molecular simulations, relative distance distributions between the haem compound I oxygen atom and H24 /H25 atoms (hydrogens on C24 and C25, respectively) were plotted. Results show large populations for O–H25 distances below 3 Å for D2 and D3 in C. cinerea in accordance with the high reactivity observed for this enzyme. In A. aegerita, however, cholecalciferol has similar populations (below 3 Å) for O–H25 and O–H24, which can justify the hydroxylation observed in C24 . In the case of ergocalciferol, due to the bulky methyl group in position C24, very few structures are found with O–H24 distances below 3 Å and thus, as expected, the reaction was only observed at the C25 position.